Public Participation in Health and Social Care: Exploring the Co-production of Knowledge - Beresford, Peter (Frontiers in Sociology, 2019)
Efforts to advance public participation in health and other policies have been associated with the production of many models and how-to-do-it guides for change. While these may have a helpful part to play in improving public and patient/user involvement in research, in this article it will be suggested that they tend to over-simplify things. Instead it is argued that an essential first step to advancing public participation in health is to put it in the context of developing modern democracy more generally. This article will seek to do this by identifying four key stages in the development of public participation in health and social care. These phases will be headlined as: 1. Working for universal suffrage in representative democracy and the achievement of social rights, like the right to decent housing, education and health; 2. Provisions for participatory democracy and community development; 3. Specific provisions for participation in health and social care; 4. State reaction and service user-led renewal as conflicts and competing agendas develop. While the proposed article will look particularly at UK developments to do this, it will also draw upon international experience and highlight the wider relevance of these phases of development. It will make connections between the extension of representative and participatory democracy, considering the different locations in which efforts to extend participation have helpfully developed, for example, in learning and training, and research and knowledge production. It will also consider how efforts to extend participation have also been undermined by pressures to tokenise and co-opt them; the continuing barriers discriminating against some groups and, ways in which service users and allies have nonetheless sought to overcome these difficulties to take forward more inclusive and diverse participation in health and social care. It will focus on some particularly promising areas of development internationally in order to do this in which co-production and the development of user-led knowledge are key.